Experimental and numerical study of expandable threaded connections and proposal of a new design. (10th April 2007) - Lo Conte, A.; Cucchetti, F.; Marangoni, M.; Quilici, C.
This paper investigates the behaviour of a flush oilfield premium connection during the cold expansion process. The objective has been to validate, through experimental tests of make up and expansion on prototypes designed traditionally, the numerical simulation generated to reproduce and interpret the mechanism that occurs during the whole process. A finite element model, able to understand the expansion mechanics, to explain the damages caused on the expanded prototypes and to define design changes in order to improve the mechanical strength and hydraulic seal, has been set up. Taking advantage of the calculation procedure, a new expandable connection has been developed, at first on the basis of numerical simulation, then assessed by means of experimental tests. The new connection has shown definitely better behaviour about the hydraulic seal, withstanding the maximum internal pressure of 5050 psi.